Literature Review: The Utilization of Augmented Reality (AR) and Virtual Reality (VR) in Learning Media at Elementary Schools - STARTYANINGSIH, THERESIA; Ervita Dwi Kusumasari; Nurhafidhoh (Schola, 2025)
ABSTRACT The advancement of technology today has transformed society into a technology-based Society 5.0 era. This development must align with current trends in the world of education. Students now expect learning experiences that incorporate innovative elements in their implementation. The use of technology-based media can serve as an alternative to support optimal learning. One such development that can be applied today involves the use of technology-based media such as Augmented Reality (AR) and Virtual Reality (VR). The use of AR and VR-based learning media has a positive impact on both the learning process and outcomes for elementary school students. AR and VR media have been proven to enhance conceptual understanding, learning motivation, engagement, and problem-solving skills through the presentation of material in a more visual, interactive, and immersive manner — although there are some technical challenges in their implementation. Keywords: Augmented Reality; Virtual Reality; Learning Media.